2021
DOI: 10.7759/cureus.15332
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Kidney Rupture: Two Case Reports With Unusual Presentations

Abstract: Two patients came to the emergency department with sudden-onset abdominal pain. The first case was a 20-year-old male; a contrast-enhanced computed tomography (CT) scan revealed a 17 cm x 7 cm hematoma in the abdomen and left retroperitoneal space. Furthermore, the left kidney was not visualized by CT. With an emergent diagnostic laparotomy, the etiology of the bleeding was determined to be left atrophichydronephrotic kidney rupture. Thus, a left nephrectomy was performed. The second case was a 38-year-old mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Finally, 10 articles were included in the study. A total of 15 cases of renal parenchyma rupture were reported in these 10 articles (Table I) (1,6,8,(10)(11)(12)(13)(14)(15)(16)). Among them, Durak et al (6) reported an autopsy case in an elderly Turkish male.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 10 articles were included in the study. A total of 15 cases of renal parenchyma rupture were reported in these 10 articles (Table I) (1,6,8,(10)(11)(12)(13)(14)(15)(16)). Among them, Durak et al (6) reported an autopsy case in an elderly Turkish male.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of cases, severe bleeding requires open surgical intervention to prevent patient mortality. When CT confirms the existence of perirenal hemorrhage, immediate surgical exploration should be performed (16). Based on the exploratory results, nephrectomy is almost always required for patients with renal tumors, renal carbuncles, hydronephrosis or severe cicatricial nephrosclerosis (10,13,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous retroperitoneal hemorrhage-hematoma (SRHH) and spontaneous renal rupture (SRR) are rare medical entities mandating urgent treatment as they can be fatal [1,2]. Nevertheless, their common clinical manifestation is abdominal pain which is not a pathognomonic finding [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…Nontraumatic retroperitoneal hemorrhage originates predominantly from the psoas muscle, followed by the kidney [1]. The most common pathology of the kidney leading to spontaneous bleeding is the presence of a tumor (benign or malignant) [2,3]. Antiphospholipid syndrome (APLS) is an autoimmune disease that causes thrombosis in the involved organs [4].…”
Section: Introductionmentioning
confidence: 99%